The effects of oral garlic on vaginal candida colony counts: a randomised placebo controlled double‐blind trial. (6th December 2013) - Watson, CJ; Grando, D; Fairley, CK; Chondros, P; Garland, SM; Myers, SP; Pirotta, M
<x xml:space="preserve">Abstract</x> Objective Garlic is effective against Candida species in vitro, and along with other alternative therapies, is used by women with vulvovaginal candidiasis. The objective of this study was to ascertain whether oral garlic reduced vaginal candida counts during the second half of the menstrual cycle in asymptomatic women colonised with Candida species. Design A simple randomised double‐blinded controlled trial. Setting Melbourne, Australia. Sample Sixty‐three asymptomatic women who were culture‐positive for Candida species at screening. Methods Participants were randomised to three garlic tablets or placebo orally, twice daily, for 14 days. Main outcome measures The primary outcome was the proportion of women with colony counts of candida >100 colony‐forming units per ml in any given day during the last 7 days before menstruation, defined as a 'case'. Secondary outcomes included the mean quantitative colony counts of candida over 14 days prior to menses. Results There was no evidence of a difference between the proportion of cases in the garlic and placebo groups (76 versus 90%; relative risk, RR 0.85; 95% confidence interval, 95% CI 0.67–1.08), in the mean colony counts in both groups (ratio of geometric means of candidal colony counts 0.63; 95% CI 0.39–10.03; P = 0.74), or difference in the number of women reporting abnormal vaginal symptoms during the 2 weeks before menstruation (RR 1.03; 95% CI 0.67–1.58; P = 0.91). The garlic group reported more adverse effects (83% compared 43% in the placebo group; difference in proportions 39%; 95% CI 17–%; P < 0.01). Conclusions This study provided data for sample size calculations in future studies on the antifungal effect of garlic, but provided no evidence to inform clinical practice regarding the use of garlic in vaginal candidiasis. Further studies might investigate longer courses or topical formulations.